DEVELOPMENT OF A VISUAL ACCOUNTING MODULE FOR HISTORICAL TOURISM MSMES IN TONDANO - Afnita, Vinda; Hutahaean, Lidia Aprileny; Manullang, Dominikus Rojoki; Sari, Ramda; Purba, Arjuna; Bako, Seven Marganda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Small and Medium Enterprises (SMEs) are a crucial pillar of the Indonesian economy, yet they often face fundamental obstacles in financial management, particularly in systematic financial recording. This study aims to develop a Simple Visual Accounting Education Module to increase financial recording awareness among SMEs in the God Bless Park and Moraya Fort historical tourism area in Tondano . This research employs the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate), limited to the development stage. The module was designed based on User-Centered Design principles and the Dual Coding Theory, integrating visual elements such as illustrations, icons, and infographics to simplify abstract accounting concepts. Development involved 20 SME actors, from initial needs identification to final product testing. The results showed that the module was highly feasible and effective, with 71.4% of users rating it